Prevalence of self-medication for dental issues in the general population: a systematic review and meta-analysis - Maiara Berlt; Karoline Brizola de Souza; Linjie Zhang; Patrícia Martins Bock; Mariana Appel Hort (Discover Public Health)
Abstract Background Dental issues may lead to the practice of self-medication as a means of providing temporary relief from symptoms, postponing or even avoiding appointments. The aim of this study was to estimate the prevalence and associated factors of dental self-medication. Methods This systematic review with meta-analysis searched the literature in four databases (MEDLINE/PubMed, SciELO, Web of Science, and Virtual Health Library), and gray literature, in mid-December 2022 and updated in January 2025. Studies were included if they had cross-sectional design and evaluated prevalence of dental self-medication. Random effect models were used to calculate prevalence estimates and their 95% CI. Results Twenty-five records were assessed for eligibility. After complete reading, 21 articles were included. The manual search yielded an additional 13 records, totaling 34 studies. Together, they included 12,985 participants. The prevalence of dental self-medication ranged from 22 to 100%, with an overall mean of 72% (95% CI: 62–80%). Toothache was the main dental condition treated by self-medication, followed by gum problems and halitosis/bad breath. Analgesics and anti-inflammatories were the most used drug classes. The variables with a positive association were female sex, age and educational level. Conclusion The prevalence of dental self-medication is high. Variations across studies likely stem from differences in definitions and sample characteristics. These findings highlight the need for public health efforts to raise awareness of the risks and promote appropriate dental care. Trial Registration The protocol for this systematic review is published in the International Prospective Register for Systematic Review (PROSPERO) database under number (CRD42022383942).